ANALISIS HUKUM TERHADAP PERBUATAN MELAWAN HUKUM ATAS PUTUSAN PERDAMAIAN DALAM PERKARA PERDATA NO. 23/Pdt.G.S/2019/PN Tka: LEGAL ANALYSIS OF AGAINST ACTIVITIES OF PEACE DECISIONS IN CIVIL CASE NO. 23/Pdt.G.S/2019/PN Tka - Nurbaity, A.; Almusawir; Tira, Andi (Faculty Of Law Bosowa University, 2021)
This study aims to determine the elements of unlawful acts against the Peace Decision No.23/Pdt.G.S/2019/PN Tka in civil cases and to find out the actions that can be taken against parties who commit acts against the law on the Peace Decision No. 23/Pdt.G.S/2019/PN Tka. The research method used is normative legal research and empirical research. Normative legal research is legal research carried out by examining library materials as the basis for research by conducting searches on regulations and literature related to the problems studied. Empirical research includes a study that seeks to identify the laws that exist in society with a view to knowing other symptoms. The results of the study indicate that the elements of unlawful acts have been fulfilled in the Peace Decision No. 23/Pdt.G.S/2019/PN.Tka where the respondent party does not pay the installments that have been determined by the judge in the peace deed and the actions taken against the party who committed an unlawful act on the Peace Decision No. 23/Pdt.G.S/2019/PN.Tka. 23/Pdt.G.S/2019/PN.Tka is to apply for execution.